Na+/K+-ATPase Activation by cAMP in the Midgut of Lutzomyia longipalpis (Lutz & Neiva, 1912; Diptera: Psychodidae). Issue 2 (10th March 2022) - Barguil Nepomuceno, Denise; DÁvila Pessoa, Grasielle Caldas; Nascimento Araújo, Ricardo; Barbosa Koerich, Leonardo; Viana Sant'Anna, Maurício Roberto; Horácio Pereira, Marcos; Figueiredo Gontijo, Nelder
Abstract: Lutzomyia longipalpis (Lutz & Neiva, 1912) females have been intensively studied regarding the regulation of midgut pH. The mechanisms involved in pH regulation are complex, and some aspects remain to be clarified. Here, we investigated the role of the Na + /K + -ATPase pump as an electrochemical potential generator and its modulation by the second messenger cAMP in the midgut of female L. longipalpis . Our results suggest that not only may Na + /K + -ATPase be the main generator of an electrochemical potential across membranes in the midgut of female L. longipalpis, but also its activity is positively regulated by cAMP. cAMP-mediated Na + /K + -ATPase pump activity might be necessary to maintain the transport of the nutrients produced during blood digestion.